2008
DOI: 10.1016/j.mathsocsci.2007.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Axiomatization of an exponential similarity function

Abstract: International audienceAn individual is asked to assess a real-valued variable y based on certain characteristics x = (x1,..., xm), and on a database consisting of n observations of (x1,..., xm, y). A possible approach to combine past observations of x and y with the current values of x to generate an assessment of y is similarity-weighted averaging. It suggests that the predicted value of y, yn+1s, be the weighted average of all previously observed values yi, where the weight of yi is the similarity between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 9 publications
(11 reference statements)
0
29
0
Order By: Relevance
“…Pape and Kurtz (2013) found that, consistent with the evidence from psychology (Shepard 1987), the similarity function has the following form, which was provided with an axiomatic foundation by Billot et al (2008). We assume this functional form here:…”
Section: The Camera and Casari (2009) Experiments And Cbsamentioning
confidence: 60%
“…Pape and Kurtz (2013) found that, consistent with the evidence from psychology (Shepard 1987), the similarity function has the following form, which was provided with an axiomatic foundation by Billot et al (2008). We assume this functional form here:…”
Section: The Camera and Casari (2009) Experiments And Cbsamentioning
confidence: 60%
“…Billot et al (2008) provide conditions on similarity-weighted averages that are equivalent to the similarity function taking the form…”
Section: Empirical Similarity Modelsmentioning
confidence: 99%
“…In addition, increasing precision might affect estimations through its perception in form of altered cautiousness (to wrongly eliminate some outcomes) with which the forecast is made and her changed confidence in this forecast 3 . If information becomes more precise, an agent's decreased cautiousness and increased confidence might allow to specify their prediction.…”
Section: Introductionmentioning
confidence: 99%
“…) intersects for all 0 ≤ z ≤ a l (defined above (12)) with the lines (g (1,3) l (z), g (2,3) l (z)) which are parallel to the line (f 1 , f 2 ) and also with all lines (g (1,2) l (z), g (1,3) l (z)) which are parallel to (f 2 , f 3 ). By Lemma B.4 this yields, that all simplicical points of the (l + 1)-th partition, which lie on the line (b 1 l+1 (1), b 3 l+1 (1)) are satisfying equation (11).…”
mentioning
confidence: 99%